Antioxidant, Anti-Tumour, and Anticoagulant Activities of Polysaccharide from Calocybe indica (APK2) - Ambika Nataraj; Sudha Govindan; Prasanna Ramani; Krishnamoorthy Akkana Subbaiah; S. Sathianarayanan; Baskar Venkidasamy; Muthu Thiruvengadam; Maksim Rebezov; Mohammad Ali Shariati; José M. Lorenzo; Mirian Pateiro (MDPI AG, 2022)
The initial structural features and in vitro biological study of crude polysaccharides from Calocybe indica (CICP) extracted by hot water followed by ethanol precipitation was investigated. High-performance gel permeation chromatography, HPLC-DAD, UV, IR and NMR spectroscopy, X-ray diffraction, scanning electron microscopy, and Congo red methods were used to determine structural features. The results revealed that CICP is a hetero-polysaccharide with a molecular weight of 9.371 × 104 Da and 2.457 × 103 Da which is composed of xylose, mannose, fucose, rhamnose, arabinose, galactose, and glucose. The antioxidant activity of CICP was evaluated using radical scavenging activity (three methods), reducing ability (three methods), metal chelating activity, and lipid peroxidation inhibition activity (two methods). It was found that the antioxidant capacity is concentration-dependent and EC50 values were found to be 1.99-3.82 mg/mL (radical scavenging activities), 0.78-2.78 mg/mL (reducing ability), 4.11 mg/mL (metal chelating activity), and 0.56-4.18 mg/mL (lipid peroxidation inhibition activity). In vitro anticoagulant assay revealed that CICP could prolong activated partial thromboplastin time (APTT), thrombin time (TT), but not prothrombin time (PT). CICP exhibited antiproliferative activity on HeLa, PC3, HT29, HepG2, and Jurkat cell lines with IC50 (μg/mL) values of 148.40, 143.60,151.00, 168.30, and 156.30, respectively. The above findings suggested that CICP could be considered a natural antioxidant and cancer preventative.